The role of central places in communal fiscal equalisation under special consideration of function-sharing cities by the example of the possible upper centre Harz - Greiving, Stefan; Fuchs, Marisa; Terfrüchte, Thomas (Raumforschung und Raumordnung | Spatial Research and Planning, 2025)
This research paper addresses the role of central places in communal fiscal equalisation and, in particular, the question of whether and, if so, how the additional burden associated with the provision of central place functions for the inhabitants of third municipalities is. For this purpose, the fiscal equalisation laws of the federal states are evaluated comparatively. While the role of central places in communal fiscal compensation is widely discussed in the spatial and financial literature, this does not apply to the specific question of the distribution of the additional burden on the municipalities involved in a function-sharing central place. The paper discusses this using the example of the proposed function-sharing upper centre consisting of the City of Halberstadt, World Heritage City Quedlinburg and the City of Wernigerode in the Harz planning region, Germany. This region has so far lacked an upper centre that is reasonably accessible and could help to ensure equal living conditions. It is argued that the distribution of the additional burden equalisation should not only consider the fiscal capacity of the municipalities involved but also their contribution to the joint fulfilment of functions, based on the respective upper-central supply function.
Keywords: Central places; Communal fiscal equalisation; Function-sharing; Harz